Leader and team behaviour during organisational change: A systems psychodynamic stance - Frans Cilliers (SA Journal of Industrial Psychology, 2006)
The aim of this research was to explore the dynamic nature of leader and team behaviour during organizational change, using five different organisational constellations or neurotic personality styles, namely the paranoid, schizoid, depressive, compulsive and histrionic styles. Qualitative research was conducted, comprising of two focus groups with eight psychologists consulting regularly to organisational change. The data was content analysed and interpreted from the systems psychodynamic stance. Each style’s leader and team behavioural manifestations are discussed. The findings and recommendations can be used by consulting psychologists towards understanding and implementing organisational change dynamics.